Role stressors, injustice and workplace incivility in banking sector: Mediating effect of negative emotion and moderating effect of self-monitoring - Lim, Hui Ling (2016)
In the context of service sector, uncivil behavior toward customers is likely to harm the effectiveness of the service provider. This study aimed at identifying the level of instigated workplace incivility in the banking sector in Malaysia, particularly in Kuala Lumpur and Penang. Built upon the stressor-emotion model of counterproductive work behavior developed by Spector and Fox in 2005, the study was also to determine the causes of instigated workplace incivility among bank employees by proposing that role conflict, role ambiguity and interactional justice might provoke uncivil behaviors through the mediation of negative emotion. In addition, self-monitoring was introduced as a moderator between negative emotion and instigated workplace incivility. Twohundred and eleven employees of commercial banks were selected using a multistage cluster sampling technique. In general, it was found that workplace incivility was not an uncommon occurrence among employees in the banking sector. The results from the structural equation modeling (SEM) showed that role conflict had a direct effect on instigated workplace incivility. This effect was partially mediated by negative emotion. Interactional justice had an impact on instigated workplace incivility through a full mediation of negative emotion. However, role ambiguity was not found to provoke a negative emotion and uncivil behaviors at all. Results also indicated that self-monitoring moderated the relationship between negative emotion and instigated workplace incivility. High self-monitors were less likely to instigate uncivil behaviors at the workplace although they encountered negative emotion. Practically, these findings could help banks in the country to mitigate the impact of role conflict and interactional justice, and incorporate self-monitoring as one of the employee selection criteria. Limitations and future directions are also highlighted in the study.